Analytical psychology : contemporary perspectives in Jungian analysis - Cambray, Joseph; Carter, Linda (Advancing theory in therapy., 2004)
Analytical Psychology, written by a range of distinguished authors takes account of advances in other fields such as neuroscience, philosophy and cultural studies and examines their effects on Jungian analytic theory.